Recent Progress in in vitro Models for Atherosclerosis Studies - Chen, Jun; Zhang, Xixi; Millican, Reid; Lynd, Tyler; Gangasani, Manas; Malhotra, Shubh; Sherwood, Jennifer; Hwang, Patrick Taejoon; Cho, Younghye; Brott, Brigitta C.; Qin, Gangjian; Jo, Hanjoong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is the primary cause of hardening and narrowing arteries, leading to cardiovascular disease accounting for the high mortality in the United States. In order to develop effective treatments for atherosclerosis, considerable efforts have been devoted to developing in vitro models. Compared to animal models, in vitro models can provide great opportunities to obtain data more efficiently, economically. Therefore, this review discusses the recent progress in in vitro models for atherosclerosis studies, including traditional two-dimensional (2D) systems cultured on the tissue culture plate, 2D cell sheets, and recently emerged microfluidic chip models with 2D culture. In addition, advanced in vitro three-dimensional models like spheroids, cell-laden hydrogel constructs, tissue-engineered blood vessels, and vessel-on-a-chip will also be covered. Moreover, the applications of these models are also summarized along with model discussion. Lastly, the future perspectives of this field are discussed.